From the page to the classroom : responses of some rural teachers and learners to textbook material on sensitive topics. - Nonkwelo, Nandipha (My University, 2012)
The research aims to investigate the responses of teachers and learners in a particular rural context to a chapter from a South African English First Additional Language textbook which is currently being developed for commercial publication. The activities and content of the chapter aim to encourage learners to think critically about power relations in teenage relationships. The material was used in two classes of Grade 11 English learners by two English teachers from the same school. Data from classroom observations, from learners’ writing and from interviews with teachers and learners was analysed in order to respond to a series of questions which focus on teachers’ and learners’ responses to a theme which was assumed to be a sensitive and controversial one and responses to the design features of the material. Firstly, the theme appeared not to be considered sensitive or controversial by either teachers or learners. Secondly, the teachers ignored almost completely the pedagogic design of the materials and in doing so negatively affected opportunities for learners to learn. Possible explanations for both findings are discussed.
Keywords: English textbooks; Sensitive topics; Teachers' pedagogy; Rural high school classrooms